THE RECONFIGURING STATE POWER THROUGH TECHNOLOGY: POLITICAL ECONOMY OF DIGITAL TRANSFORMATION IN PUBLIC SECTOR - Hwihanus; Narastri, Maulidah; Hidayat, Muhammad Taufiq (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The rapid advancement of digital technology has reshaped how governments manage resources, deliver services, and exercise authority. This study explores the political economy dynamics of digital transformation within Indonesian public institutions, focusing on how technology reconfigures the distribution of power, accountability mechanisms, and institutional performance. Based on field data from government agencies undergoing digital reform, the research highlights how the adoption of information systems and digital tools is not merely a technical endeavor, but also a political process influenced by institutional interests, bureaucratic resistance, and policy incentives. The findings reveal that while digital transformation can enhance transparency and efficiency, its success depends on the alignment of political will, institutional capacity, and technological adaptability. This paper contributes to the broader discourse on digital governance by framing digital transformation as both a means of administrative modernization and a site of power negotiation within the state apparatus.